De la structure tribale à la décentralisation régionale - Salima Salhi (Belgeo)
This article examines the evolution of Morocco’s territorial organization throughout the pre-colonial, colonial, and post-colonial periods. It highlights the impact of the country’s historical trajectory on the decentralization and deconcentration reforms undertaken since its independence in 1956. Before the arrival of the French, Morocco operated under a form of primary decentralization, embodied by the Jemâas, who managed local affairs within the tribes. However, colonization introduced a centralized model that limited the autonomy of local administrative entities. After independence, Morocco undertook reforms aimed at breaking with this colonial legacy and promoting the balanced development of the country. These reforms have been gradual and include the adoption of new constitutions, the implementation of decentralization and regionalization, and charters aimed at regulating local public action. Despite these efforts, the results in terms of economic and social development have not always lived up to expectationsThe article is based on extensive research, including consultations of diplomatic archives of the French protectorates in Morocco and analysis of laws and reforms. Maps have also been developed to better understand the evolution of Morocco’s territorial organization. This research provides a solid basis for an in-depth analysis of the Moroccan territorial organization system and paves the way for future studies aimed at enriching this understanding.